LINE1 insertions as a genomic risk factor for schizophrenia: Preliminary evidence from an affected family. Issue 4 (16th March 2016) - Guffanti, Guia; Gaudi, Simona; Klengel, Torsten; Fallon, James H.; Mangalam, Harry; Madduri, Ravi; Rodriguez, Alex; DeCrescenzo, Paula; Glovienka, Emily; Sobell, Janet; Klengel, Claudia; Pato, Michele; et al.
Abstract : Recent studies show that human‐specific LINE1s (L1HS) play a key role in the development of the central nervous system (CNS) and its disorders, and that their transpositions within the human genome are more common than previously thought. Many polymorphic L1HS, that is, present or absent across individuals, are not annotated in the current release of the genome and are customarily termed "non‐reference L1s." We developed an analytical workflow to identify L1 polymorphic insertions with next‐generation sequencing (NGS) using data from a family in which SZ segregates. Our workflow exploits two independent algorithms to detect non‐reference L1 insertions, performs local de novo alignment of the regions harboring predicted L1 insertions and resolves the L1 subfamily designation from the de novo assembled sequence. We found 110 non‐reference L1 polymorphic loci exhibiting Mendelian inheritance, the vast majority of which are already reported in dbRIP and/or euL1db, thus, confirming their status as non‐reference L1 polymorphic insertions. Four previously undetected L1 polymorphic loci were confirmed by PCR amplification and direct sequencing of the insert. A large fraction of our non‐reference L1s is located within the open reading frame of protein‐coding genes that belong to pathways already implicated in the pathogenesis of schizophrenia. The finding of these polymorphic variants among SZ offsprings is intriguing and suggestive of putative pathogenic role. Our data show the utility of NGS to uncover L1 polymorphic insertions, a neglected type of genetic variants with the potential to influence the risk to develop schizophrenia like SNVs and CNVs. © 2016 Wiley Periodicals, Inc.